Revisiting DDR in Liberia: exploring the power, agency and interests of local and international actors in the 'making' and 'unmaking' of combatants - Munive, Jairo; Jakobsen, Stine Finne (Conflict, security & development, 2012)
The understanding that disarmament, demobilisation and reintegration (DDR) programmes are essential in helping to prevent war recurrence in post-conflict situations is at the heart of current international aid practice and the academic literature on peacekeeping and stabilisation. However DDR programmes are often launched on the basis of untested assumptions. This article considers the DDR programme in Liberia and analyses the complex relationship between the programmatic efforts to disarm and reintegrate combatants and the programme's actual effects. If we are to understand how DDR works as a tool of post-conflict governance, it is essential to explore the mechanisms of authority and power at stake. The focus is therefore not on whether combatants were successfully disarmed and reintegrated, but rather on exploring unfolding processes and the field of forces within which DDR programmes are implemented. It critically assesses the ideas of disarmament and reintegration and the basic assumptions behind current DDR policy through an analysis of the Liberian case, emphasising the agency and interests of local and international actors in the 'making' and 'unmaking' of combatants.